Analisis Keausan Pada Pahat Mesin Perkakas Menggunakan Sinyal Suara - Karjuni Karjuni; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Machining processes in manufacturing industries such as machine tools required special monitoring during the operation process. Cutting tool is a component that needs to be monitored, because it is a part that often suffered damage or wear. In this research the Monitoring is conducted to determine the damage or wear that occurs on the tool HSS lathe and drill. The method used is the indirect method, where the sound signal is recorded by using the microphone as a sensor through the software. The obtained sound signal is then processed by using fast fourier transform (FFT). The results show that there is a difference in the amplitude value of time domain signal and frequency domain. The tendency is the more wearness, the higher the amplitude of sound signal which can be seen clearly in time domain and frequency domain.Keywords : Tool Wear, Sound Signals, Machine Tools, FFT